Zoanthid housekeeping: some nomenclatural notes on the Zoantharia (Cni-daria: Anthozoa: Hexacorallia) - Low, Martyn E. Y.; Reimer, James Davis (Zootaxa, 2012)
The identities, authorship and/or spellings of three genusand three family-group names in the order Zoantharia (=Zoanthidea), are clarified. Palythoa axinellae Schmidt, 1862, is designated as the type species of Heterozoanthus Verrill,1870, making this genus-group name an objective synonym of Parazoanthus Haddon & Shackleton, 1891, with prevailingusage of the latter maintained by a reversal of precedence. The family-group name Heterozoanthidae was inadvertentlyestablished by Pax & Müller (1956), and is a junior objective synonym of Parazoanthidae Delage & Hérouard, 1901. Thegenusand family-groups names Mardoell and Mardoellidae (both established by Danielssen 1890) are respectivesynonyms of Epizoanthus Gray, 1867, and Epizoanthidae Delage & Hérouard, 1901, with prevailing usage of the last-named family-group conserved by a reversal of precedence. The genus-group name Mardoellia Blanchard, 1893, is anunjustified emendation and objective synonym of Mardoell Danielssen, 1890. Rafinesque (1815) and not Gray (1832, 1840) is the author of the family-group name Zoanthidae.